A interação entre a fertilidade do solo e a massa da semente influencia os atributos funcionais de espécies arbóreas tropicais? - Gomez Beltran, Liseth Ana Délia (2017)
Biological, physical and chemical characteristics of the soil are environmental filters that strongly influence the composition of the plant communities. The knowledge of the effect of soil conditions on the survival and growth of plant species is important for the recovery activities in degraded areas. These aspects of plant performance are directly related to the functional characteristics of species, so understanding the responses of the different resources to different soil conditions can help to choose species that are best suited to each area. We have carried out an experiment in nursery with the objective of evaluating the influence of different soil treatments on survival and functional characteristics; Leaf Area (LA), Specific Leaf Area (SLA), Leaf Dry Matter Content (LDMC), Root Mass Fraction (RMF), Specific Root Length (SRL) and Relative Height Increment (RHI) of eleven native forest species forming a seed mass gradient. The treatments used in the experiment were control soil - without the addition of any fertilizer (CT); addition of chemical fertilizer - NPK (QU); addition of organic fertilizer (OR) and the addition of chemical fertilizer and organic fertilizer (OQ). Soil chemical attributes in the four treatments were evaluated after two and seven months after planting to verify the changes that occurred over time. In addition, we evaluated soil chemical attributes of natural areas of occurrence of these species, preserved and degraded forests. The monitoring of the experiment was performed for four months and at the end of this period we recorded survival and measured the functional characteristics of all species. Chemical soil attributes used in the treatments CT and QU were more similar to the attributes of the areas used as reference, showing higher values of acidity potential (H + Al) and cation exchange capacity (CTC), and lower values of nitrogen (N) and organic matter. The seed mass heavily influenced survival in CT, QU and OR treatments and did not differed between CT and QU treatments and, furthermore, in OR treatment the survival was greater than in CT and QU treatments. The effect of seed mass on survival was not significant in OQ treatment. We detected a high positive correlation between SLA, RMF and SRL that were negatively correlated with LA and RHI. The functional properties of the species differed between treatments, but no differences were detected between treatments OR and OQ. In these two treatments, species reached higher values of LA and RHI and lower values of SRL, RMF and SLA than other treatments. Functional attributes varied between and within species. Phenotypic plasticity was higher in LA, RHI, SRL and RMF, and the variation of LA, RHI and SRL were highly correlated with each other and together were negatively related to seed mass. This study showed that limited terrestrial resources were able to modify root 12 architecture, leaf traits and the rate of growth of the aerial parts, which suggests that plants should invest more in fundraising bodies to increase the chances of survival. Intra-specific variation of LA, RHI, SRL, RHI and LDMC characteristics were correlated with each other and negatively correlated with seed mass. Smaller seed species were more plastic than larger seed species. In the treatment CT, these species reached higher values of SLA and SRL, while treatments with organic matter addition, these species reach higher values of LA and RHI. The addition of organic matter in the soil increased the survival and growth of plants, in particular small seed species. Thus, the addition of organic matter as pre-planting treatment proved to be more efficient to increase the performance of native tree species. However, experiments under field conditions are necessary to quantify the efficacy of manure on the reintroduction of native species into deforested forests.